Additions to “The Cypriniformes Tree of Confusion” - Britz, Ralf; Conway, Kevin W. (Zootaxa, 2011)
Since the acceptance of our paper (Britz & Conway 2011), two publications have appeared that have relevance to the topic discussed and need to be mentioned. Mabee et al. (2011) is the first morphological phylogenetic analysis produced by the Cypriniformes Tree of Life project and covers 62 characters from gill arch, and hyoid osteology in 53 cypriniform taxa. Tang et al.’s (2011) molecular analysis of the cyprinid subfamily Gobioninae also included the three miniature taxa Sundadanio, Paedocypris and Danionella and was based on two mitochondrial and two nuclear genes. Their parsimony analysis recovered all three taxa in the cyprinid subfamily Danioninae, with Paedocypris and Danionella as sister groups, with this clade forming the sister group to a clade comprising Sundadanio and Esomus. Their maximum likelihood analysis confirmed their placement in danionines and found Paedocypris as the sister group to Sundadanio, and Danionella as the sister group of Danio rerio, Devario auropurpureus and Microrasbora rubescens. Their partitioned Bayesian analysis, however, recovered Sundadanio as the sister group of Leptobarbus, Danionella as the sister group to Danio, Devario and Microrasbora, and Paedocypris as the sister group to all other Cypriniformes, as did Mayden & Chen (2010). This remarkable difference in the position of the three taxa between the different trees was not even mentioned or discussed except in the brief remark relating only to Paedocypris (p. 11): “The Bayesian results agree on a monophyletic Cypriniformes, but recover a putative cyprinid (Paedocypris) as the sister group to all other cypriniform fishes.”